Kewarganegaraan dan Pengakuan Budaya Lokal : Tantangan Multikulturalisme di Era Modern Indonesia - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; Maulana Zidane Saputra; Paramitha Maulida Sifa; Ika Diyah Mawarni (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Purpose of the Study :This study aims to explore the challenges of multiculturalism in Indonesia within the context of citizenship and the recognition of local cultures. It focuses on how cultural diversity can be managed to form an inclusive national identity and address issues such as marginalization, homogenization, and ethnic conflicts. Methodology : The research employs a literature review and qualitative analysis of primary and secondary sources. Data was gathered through a review of existing literature, interviews with community leaders, and observation of public policies related to multiculturalism in Indonesia. Findings : The study reveals that marginalization of local cultures and homogenization due to globalization are major challenges. Conflicts between ethnic groups have also increased due to tensions related to cultural and economic differences. Current public policies do not fully reflect the country's cultural diversity. Conclusion : To address these challenges, it is necessary to strengthen multicultural education, preserve local cultures, and foster intercultural dialogue. Effective management of globalization's impact is also crucial to maintaining cultural diversity. With these measures, Indonesia can build an inclusive and harmonious national identity while reinforcing social cohesion.